Hepatic epitheloid haemangioendothelioma: a rare malignant tumour. Issue 1 (28th January 2020) - Lund, Pernille Strecker; Willemoe, Gro Linno; Hansen, Lasse Bremholm; Warnecke, Mads
Abstract : Our case concerns a 66-year-old man. After experiencing recurrent episodes of abdominal pain, an initial CT scan, ultrasound and gastroscopy was carried out. All of which showed normal findings. As a consequence of persisting symptoms, another CT scan was performed. This scan revealed a hypodense area in the right lobe of the liver. This was interpreted as a possible haemangioma. Subsequent MRI scans indicated an intrahepatic cholangiocarcinoma. A final ultrasound-guided liver biopsy was performed and histology demonstrated epitheloid haemangioendothelioma, which was locally advanced and inoperable.